2D Phosphorene: Epitaxial Growth and Interface Engineering for Electronic Devices. Issue 47 (13th August 2018) - Zhang, Jia Lin; Han, Cheng; Hu, Zehua; Wang, Li; Liu, Lei; Wee, Andrew T. S.; Chen, Wei
Abstract: Black phosphorus (BP), first synthesized in 1914 and rediscovered as a new member of the family of 2D materials in 2014, combines many extraordinary properties of graphene and transition‐metal dichalcogenides, such as high charge‐carrier mobility, and a tunable direct bandgap. In addition, it displays other distinguishing properties, e.g., ambipolar transport and highly anisotropic properties. The successful application of BP in electronic and optoelectronic devices has stimulated significant research interest in other allotropes and alloys of 2D phosphorene, a class of 2D materials consisting of elemental phosphorus. As an atomically thin sheet, the various interfaces presented in 2D phosphorene (substrate/phosphorene, electrode/phosphorene, dielectric/phosphorene, atmosphere/phosphorene) play dominant roles in its bottom‐up synthesis, and determine several key characteristics for the devices, such as carrier injection, carrier transport, carrier concentration, and device stability. The rational design/engineering of interfaces provides an effective way to manipulate the growth of 2D phosphorene, and modulate its electronic and optoelectronic properties to realize high‐performance multifunctional devices. Here, recent progress of the interface engineering of 2D phosphorene is highlighted, including the epitaxial growth of single‐layer blue phosphorus on different substrates, surface functionalization of BP for high‐performance complementary devices, and the investigation of the BP degradation mechanism in ambient air. Abstract : Due to the atomically thin nature of 2D phosphorene, its growth process, fundamental properties, and device performance are dominated by the various interfaces presented. Recent development in the interface engineered epitaxial growth of 2D phosphorene, surface functionalization of black phosphorus (BP)‐based electronic devices, and degradation mechanisms of BP under a well‐controlled environment are reviewed.